Non-comparative evaluation of the safety of aerosolized amphotericin B lipid complex in patients undergoing allogeneic hematopoietic stem cell transplantation - Alexander, B.D.; Dodds Ashley, E.S.; Addison, R.M.; Alspaugh, J.A.; Chao, N.J.; Perfect, J.R. (Transplant infectious disease, 2006)
: Allogeneic hematopoietic stem cell transplant (HSCT) recipients are at increased risk for invasive fungal infections (IFIs) over prolonged periods of time. Aerosolized amphotericin B lipid complex (ABLC) has shown promise in lung transplant recipients as a convenient means of delivering protective drug to the upper airways avoiding systemic toxicities. The safety and tolerability of aerosolized ABLC in 40 subjects undergoing allogeneic HSCT was prospectively investigated in an open‐labeled, non‐comparative study. Subjects received aerosolized ABLC treatment once daily for 4 days, then once weekly for 13 weeks; fluconazole was administered daily as standard of care through post‐transplant day 100. Pulmonary mechanics were measured before and after each dose of inhaled ABLC; adverse events (AEs) and the development of IFI were also monitored. Cough, nausea, taste disturbance, or vomiting followed 2.2% of 458 total inhaled ABLC administrations; 5.2% of inhaled ABLC administrations were associated with ≥20% decrease in pulmonary function measurements (forced expiratory volume in 1 second or forced vital capacity) and none required treatment with bronchodilators or withdrawal from study. Four mild AEs were considered possibly or probably related to study treatment; no deaths or withdrawals from treatment were attributed to study drug. Of 3 proven IFIs occurring during the study period, only 1, a catheter‐related case of disseminated fusariosis, occurred while the subject was receiving study medication. Aerosolized ABLC was well tolerated in allogeneic HSCT recipients. With only 1 of 40 subjects developing IFI while receiving treatment, the combination of fluconazole and inhaled ABLC warrants further study as antifungal prophylaxis following allogeneic HSCT.